2018
DOI: 10.20473/ijtid.v7i1.6311
|View full text |Cite
|
Sign up to set email alerts
|

CRYPTOCOCCAL ANTIGENEMIA IN HIV/AIDS PATIENTS USING LATERAL FLOW IMMUNOASSAY DETECTION AT Dr. SOETOMO GENERAL HOSPITAL SURABAYA

Abstract: Cryptococcus  infection in HIV / AIDS patients results in cryptococcal meningitis, a major cause of subacute meningitis  with 100% mortality if not receiving appropriate antifungal therapy. An examination of cryptococcal antigen will provide risk information for patients who will experience cryptococcal meningitis. Better diagnosis in asymptomatic and symptomatic phases of cryptococcosis are key components to reduce morbidity and mortality. This study aims to determine the proportion of cryptococcal antigenemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…By using antigen detection, a higher diagnostic sensitivity and incidence is obtained 42,43 . Four studies on the detection of antigenaemia among ART naïve HIV patients conducted in Jakarta, Bandung, Surabaya showed the prevalence of antigenaemia varied between 6.4%–7.3% 41,42,69 . Another study conducted in Pontianak, Kalimantan (Borneo) found the prevalence of antigenaemia to be 5.6% among HIV‐infected patients 70 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using antigen detection, a higher diagnostic sensitivity and incidence is obtained 42,43 . Four studies on the detection of antigenaemia among ART naïve HIV patients conducted in Jakarta, Bandung, Surabaya showed the prevalence of antigenaemia varied between 6.4%–7.3% 41,42,69 . Another study conducted in Pontianak, Kalimantan (Borneo) found the prevalence of antigenaemia to be 5.6% among HIV‐infected patients 70 .…”
Section: Discussionmentioning
confidence: 99%
“…42,43 Four studies on the detection of antigenaemia among ART naïve HIV patients conducted in Jakarta, Bandung, Surabaya showed the prevalence of antigenaemia varied between 6.4%-7.3%. 41,42,69 Another study conducted in Pontianak, Kalimantan (Borneo) found the prevalence of antigenaemia to be 5.6% among HIV-infected patients. 70 In our department, we recorded cases of cryptococcosis in non-HIV patients.…”
Section: Cryptococcosismentioning
confidence: 99%
“…6 Prevalensi MK pada penderita HIV tahun 2018 dilaporkan sebesar 7,1% di Bandung dan 7,32% di Surabaya. 7,8 Jamur Cryptococcus dapat ditemukan di alam dan bersifat saprofit. Cryptococcus neoformans CDK-292/ vol.…”
Section: Etiologiunclassified